68Ga-P15-041, A Novel Bone Imaging Agent for Diagnosis of Bone Metastases - Rui Guo (Frontiers Media S.A., 2021)
Objectives68Ga-P15-041 (68Ga-HBED-CC-BP) is a novel bone-seeking PET radiotracer, which can be readily prepared by using a simple kit formulation and an in-house 68Ga/68Ge generator. The aim of this study is to assess the potential human application of 68Ga-P15-041 for clinical PET/CT imaging and to compare its efficacy to detect bone metastases of different cancers with 99mTc-MDP whole-body bone scintigraphy (WBBS).MethodsInitial kinetic study using Patlak analysis and parametric maps were performed in five histopathologically proven cancer patients (three males, two females) using 68Ga-P15-041 PET/CT scan only. Another group of 51 histopathologically proven cancer patients (22 males, 29 females) underwent both 99mTc-MDP WBBS and 68Ga-P15-041 PET/CT scans within a week, sequentially. Using either pathology examination or follow-up CT or MRI scans as the gold standard, the diagnostic efficacy and receiver operating characteristic curve (ROC) of the two methods in identifying bone metastases were compared (p <0.05, statistically significant).ResultsFifty-one patients were imaged, and 174 bone metastatic sites were identified. 68Ga-P15-041 PET/CT and 99mTc-MDP WBBS detected 162 and 81 metastases, respectively. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of 68Ga-P15-041 PET/CT and 99mTc-MDP WBBS were 93.1% vs 81.8%, 89.8% vs 90.7%, 77.5% vs 69.2%, 97.2% vs 93.4% and 90.7% vs 88.4%, respectively. Our results showed that the mean of SUVmax was significantly higher in metastases than that in benign lesions, 15.1 ± 6.9 vs. 5.6 ± 1.3 (P <0.001). Using SUVmax = 7.6 as the cut-off value by PET/CT, it was possible to predict the occurrence of metastases (AUC = 0.976; P <0.001; 95% CI: 0.946–0.999). However, it was impossible to distinguish osteoblastic bone metastases from osteolytic bone lesions. Parametric maps based on Patlak analysis provided excellent images and highly valuable quantitative information.Conclusions68Ga-P15-041 PET/CT, offering a rapid bone scan and high contrast images in minutes, is superior to the current method of choice in detecting bone metastases. It is reasonable to suggest that 68Ga-P15-041 PET/CT could become a valuable routine nuclear medicine procedure in providing excellent images for detecting bone metastases in cancer patients. 68Ga-P15-041 could become a valuable addition expanding the collection of 68Ga-based routine nuclear medicine procedures where 18F fluoride is not currently available.